(untitled) (Journal of the College of Languages (JCL), 2025)
The problem of rebellion is considered one of the features of rapid changes that a society undergoes in all spheres and directions of life, especially in the realm of social relations, customs, traditions, values, and principles. Rebellion may manifest itself in rebellion against oneself, against values or traditions, or against social or governmental authority. One may find that submission plays a vital role in all of these interactions. This study deals with the problem of rebellion in the works of two renowned authors: The French Gustave Flaubert and the Israeli Amos Oz, through two main characters who share similar qualities and traits. Emma Bovary and Henna Konin demonstrate this through their rebellion against themselves, their relationship with society and family, and their relationship with customs and traditions. They appeared in manifestations of rebellion at times and submission at others. Rebellion and submission also emerged through the two authors’ relationship. It seems that the two authors’ connection in the rebellion issue was characterized by behavioral and psychological issues, which resulted from physiological and psychological changes that influenced their conduct and gave rise to severe psychological difficulties. They felt lost and alienated because they were unable to face them. As a result, they rebelled against traditions, values, and practices, which in turn led to unacceptable aggressive tendencies. This, in turn, led to the two characters’ tendency towards rebellion and revolution against authority, whether that of the family or society in general. תקציר בעיית המרד היא טבעם של השינויים המהירים שעוברים על החברה בכל תחומי החיים וכיווניהם, במיוחד בתחום היחסים החברתיים, המנהגים, המסורות, הערכים והעקרונות וכו’. מרד יכול להתבטא כמרד עצמי, מרד נגד מנהגים, מרד נגד עקרונות ונורמות, או מרד נגד כוח פוליטי או חברתי. אנו עשויים למצוא כניעה לקחת מקום חשוב בכל מערכות היחסים האלה. במחקר זה נתייחס לתופעה של מרד בקרב שני סופרים בולטים, גוסטב פלובר הצרפתי ועמוס עוז הישראלי. דרך שתי גיבורות שחלקו את אותן תכונות ומאפיינים. הגיבורות "אמה בובארי וחנה גונין" הראו זאת באמצעות המרד העצמי שלהן כדי להוכיח את קיומן, באמצעות מערכת היחסים שלהן עם החברה והמשפחה, וגם מרדו נגד מנהגים ומסורות. הן היו בצורה הגדולה ביותר של מרד, וכניעה שוב. מרד וכניעה הופיעו גם באמצעות מערכת היחסים של שני הסופרים עם השלטון. נראה כי הקשר בין שני הסופרים בבעיית המרד נוצר כתוצאה מבעיות פסיכולוגיות והתנהגותיות, בשל השינויים הפיזיולוגיים והפסיכולוגיים שהשפיעו על התנהגותם, מה שהוביל להופעתם של קונפליקטים פסיכולוגיים חמורים. הם לא יכלו להילחם בזה, והם הרגישו מנוכרים ואבודים. כל זה הוביל למרד שלהם נגד ערכים, מנהגים ומסורות. זה מה שאנו יודעים על נטייתם של שתי הגיבורות להתנגד ולמרד, על ידי הצגת נטיות לעצמאות ולמרד נגד השלטון, בין אם זה בסמכותה של המשפחה, או בחברה בכלל.